Hubungan anatara pengetahuan dan status ekonomi terhadap pemakaian alat pelindung diri pada pemulung sampah di TPA Tamangapa Kota Makassar - Qasim, Muhammad - (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
One form in avoiding the occurrence of occupational diseases and workplace accidents is to understand the use of PPE and wear personal protective equipment. Use of the intended personal protective equipment in which the scavenger conditions in the Tamangapa TPA while working with masks, boots, gloves and protective helmets. With the aim of preventing contamination of the disease and protecting the part or whole body there is a potential danger. This study aims to determine the relationship of knowledge and social economy to the use of personal protective equipment in garbage scavengers in TPA Tamangapa Makassar City. This research was conducted in TPA Tamangapa Kota Makassar. The research was conducted in January until February 2018. The research design used was analytic observational method is a research design that aims to see the relationship of two variables or without any treatment or intervention with cross sectional approach with the number of samples was 99 respondents according to the inclusion and exclusion criteria. Data collection using questionnaire and data analysis using statistic with chi square test. The result of bivariate analysis showed that there was a correlation of knowledge with the use of self-protective device p = 0.024, and there was an economic status relationship with the use of Personal Protective Equipment (p = 0,029). Conclusion there is a relationship between knowledge, and economic status of garbage scavengers in TPA Tamangapa Makassar City. It is advisable to garbage collectors to further improve their understanding and discipline of using Personal Protective Equipment when working. One form in avoiding the occurrence of occupational diseases and workplace accidents is to understand the use of PPE and wear personal protective equipment. Use of the intended personal protective equipment in which the scavenger conditions in the Tamangapa TPA while working with masks, boots, gloves and protective helmets. With the aim of preventing contamination of the disease and protecting the part or whole body there is a potential danger. This study aims to determine the relationship of knowledge and social economy to the use of personal protective equipment in garbage scavengers in TPA Tamangapa Makassar City. This research was conducted in TPA Tamangapa Kota Makassar. The research was conducted in January until February 2018. The research design used was analytic observational method is a research design that aims to see the relationship of two variables or without any treatment or intervention with cross sectional approach with the number of samples was 99 respondents according to the inclusion and exclusion criteria. Data collection using questionnaire and data analysis using statistic with chi square test. The result of bivariate analysis showed that there was a correlation of knowledge with the use of self-protective device p = 0.024, and there was an economic status relationship with the use of Personal Protective Equipment (p = 0,029). Conclusion there is a relationship between knowledge, and economic status of garbage scavengers in TPA Tamangapa Makassar City. It is advisable to garbage collectors to further improve their understanding and discipline of using Personal Protective Equipment when working.